2015
DOI: 10.1038/ncomms7692
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 alters T-cell metabolic reprogramming by inhibiting glycolysis and promoting lipolysis and fatty acid oxidation

Abstract: During activation, T cells undergo metabolic reprogramming, which imprints distinct functional fates. We determined that on PD-1 ligation, activated T cells are unable to engage in glycolysis or amino acid metabolism but have an increased rate of fatty acid β-oxidation (FAO). PD-1 promotes FAO of endogenous lipids by increasing expression of CPT1A, and inducing lipolysis as indicated by elevation of the lipase ATGL, the lipolysis marker glycerol and release of fatty acids. Conversely, CTLA-4 inhibits glycolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
805
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 939 publications
(879 citation statements)
references
References 61 publications
28
805
1
6
Order By: Relevance
“…We hypothesized that FAO would be lower in Pdl1 -/-donor T cells because PD-1 ligation of activated T cells can limit glycolysis and amino acid metabolism while increasing FAO (45), and GVHD Teffs are under high metabolic stress and known to utilize FAO to provide energy for their survival and/or function. We first measured FA uptake using BoDipy C1-C12 , a fluorescent FA analog, and found that it was significantly reduced in Pdl1 -/-donor T cells ( Figure 10A).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that FAO would be lower in Pdl1 -/-donor T cells because PD-1 ligation of activated T cells can limit glycolysis and amino acid metabolism while increasing FAO (45), and GVHD Teffs are under high metabolic stress and known to utilize FAO to provide energy for their survival and/or function. We first measured FA uptake using BoDipy C1-C12 , a fluorescent FA analog, and found that it was significantly reduced in Pdl1 -/-donor T cells ( Figure 10A).…”
Section: Discussionmentioning
confidence: 99%
“…The PD-1/PD-L1 axis is known to mediate peripheral tolerance and attenuation of acute inflammatory responses through modulation of T-cell receptor (TCR) signal transduction, metabolic reprogramming, anergy and apoptosis (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 is also expressed on melanoma cells, and its binding to PD-L1 augments glucose uptake and glycolysis through activation of the mTOR signaling pathway [53,67]. Intriguingly, PD-1 ligation on T cells has the opposite effect of blocking glycolysis [68], and thus impeding glycolysis-dependent effector functions [54]. Thus, PD-1/PD-L1 checkpoint blockade not only terminates an inhibitory signal on TIL but also indirectly boosts the activity of these T cells by increasing intratumoral glucose availability as a consequence of limiting glucose consumption by the tumor cells.…”
Section: Immunotherapies Overcome Tumor-induced Immunosuppressionmentioning
confidence: 99%